(untitled) (International Journal of Engineering and Computer Science, 2017)
: This paper discusses various versions of TCP and their congestion control algorithm changes in TCP’s existing congestion control, limitation of older version of TCP variants. We discuss new version of TCP called TCP Westwood with sender side modification of the window congestion control scheme TCP Westwood continuously estimate at sender side packet rate of connection by monitoring ACK reception rate. In this paper we reviewed the comparison of performance of TCP Reno with TCP Westwood in good link and lossy link. In this paper we have discussed the fairness and friendliness issue of TCP Westwood. Also we discuss the mechanism called agile probing that improves the performance of TCP Westwood in slow start phase. This method improves the startup performance of TCP Westwood. This method improves the performance of TCP Westwood in congestion avoidance phase as well as when large amount of bandwidth that suddenly becomes available